Can the Central Bank Alleviate Fiscal Burdens? - Ricardo Reis (Center for Economic Studies and ifo Institute (CESifo), 2017)
Central banks affect the resources available to fiscal authorities through the impact of their policies on the public debt, as well as through their income, their mix of assets, their liabilities, and their own solvency. This paper inspects the ability of the central bank to alleviate the fiscal burden by inuencing different terms in the government resource constraint. It discusses five channels: (i) how inflation can (and cannot) lower the real burden of the public debt, (ii) how seignorage is generated and subject to what constraints, (iii) whether central bank liabilities should count as public debt, (iv) how central bank assets create income risk, and whether or not this threatens its solvency, and (v) how the central bank balance sheet can be used for fiscal redistributions. Overall, it concludes that the scope for the central bank to lower the fiscal burden is limited.
Keywords: E58; E63; E52; 330; monetary policy; reserves; interest rates; quantitative easing